2017
DOI: 10.29312/remexca.v0i14.459
|View full text |Cite
|
Sign up to set email alerts
|

Diagnóstico del proceso de reforestación en manglares de la costa de Tabasco

Abstract: En México la superficie de manglar se reduce a una tasa anual de 2% para la vertiente del Pacifico y 2.8% para el Golfo de México. Sin embargo, los procesos de restauración son más lentos que la velocidad con la que se pierden. En Tabasco se ha invertido en programas de reforestación a través de la CONAFOR para reforestar superficies de manglar con resultados no acordes a las metas planteadas, lo cual es alarmante si se considera que tales actividades son prioritarias para mitigar lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
3
0
1
Order By: Relevance
“…One of the first experimental studies on the effect of the mineralogy on the ISC process using recombined crude oil and reservoir rock samples from the FPO and its comparison with inert sand was presented by Hernández (2003) . Results of this study indicated that the oil recovery factors of the experiments by using reservoir sand and inert sand samples were similar, with 90% for both cases under ideal laboratory conditions.…”
Section: Description Of the Isc Projects In Venezuelamentioning
confidence: 75%
See 1 more Smart Citation
“…One of the first experimental studies on the effect of the mineralogy on the ISC process using recombined crude oil and reservoir rock samples from the FPO and its comparison with inert sand was presented by Hernández (2003) . Results of this study indicated that the oil recovery factors of the experiments by using reservoir sand and inert sand samples were similar, with 90% for both cases under ideal laboratory conditions.…”
Section: Description Of the Isc Projects In Venezuelamentioning
confidence: 75%
“…Results of this study indicated that the oil recovery factors of the experiments by using reservoir sand and inert sand samples were similar, with 90% for both cases under ideal laboratory conditions. Nevertheless, Hernández (2003) indicated that the results obtained with the reservoir sand samples showed an increase in the temperature of the combustion front and a decrease in the advance speed of the front; in the same way, it was pointed out that the high viscosity of the crude oil generated operational problems when starting the heating for ignition; a final fraction of the recovered crude oil showed an improvement of the oil properties, related to an increase in its API gravity and a reduction in viscosity …”
Section: Description Of the Isc Projects In Venezuelamentioning
confidence: 98%
“…Estos autores describen que las podas intensas tienen efectos negativos en planta, de ahí la importancia de no sobrepasar la poda del 30 o 40 % del total de yemas. Dentro de los efectos negativos que con mayor frecuencia se reportan destaca la reducción del incremento diamétrico y la emisión de numerosas ramas epicrmicas (Hernández Melchor, et al 2016).…”
Section: Discussionunclassified
“…To implement a proper infrastructure for all economic sectors, the national regulatory framework contemplates as mandatory to establish technical feasibility studies that frame social, economic, and environmental issues, all of them reflected in an Environmental Impact Manifest (MIA). Though, most of these studies have been carried out without multidisciplinary approaches, being mostly technical analysis (Martínez-Zurimendi et al, 2015;Hernández Melchor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%